Obesity and Type 2 Diabetes Alters the Immune Properties of Human Adipose Derived Stem Cells. (4th July 2016) - Serena, Carolina; Keiran, Noelia; Ceperuelo-Mallafre, Victoria; Ejarque, Miriam; Fradera, Rosa; Roche, Kelly; Nuñez-Roa, Catalina; Vendrell, Joan; Fernández-Veledo, Sonia
Abstract: Adipose tissue-derived stem cells (ASCs) are proposed as an alternative stem cell source to bone marrow-derived cells for immune cell therapy. However, microenvironmental factors may impact the functionality of this population in human adipose tissue (AT). We hypothesized that the fat depot in addition to the donor phenotype controls the immunomodulatory capacity of ASCs. Focusing on obesity and type 2 diabetes (T2D) as metabolic disorders that might affect the immune response of ASCs, we compared the inflammatory response of ASCs from subcutaneous and visceral AT of age-matched donors (lean n = 4, body mass index [BMI] 21.98 ± 1.9; obese n = 4 BMI 33.1 ± 2.1 and T2D n = 4 BMI 35.3 ± 1.5). Obese and particularly T2D-derived ASCs showed increased expression of inflammatory markers, activation of NLRP3 inflammasome and higher migration, invasion and phagocytosis capacities than those derived from lean donors. Remarkably, ASCs derived from obese and T2D subjects exhibited a reduction in typical immunosuppressive activities attributed to stem cells. Accordingly, obese and T2D-ASCs were less effective in suppressing lymphocyte proliferation, activating the M2 macrophage phenotype, and in increasing TGF-β1 secretion, than lean-derived ASCs. Treatment of lean hASCs with interleukin (IL)-1β mimicked the dysfunctional immune behavior of obese and T2D hASCs. Conversely, combined treatment with IL1RA and TGF-β1 reverted the phenotype of obese- and T2D-ASCs. These data indicate that the donor metabolic phenotype compromises the immunomodulatory properties of ASCs. These results are relevant not only for understanding the physiology of ASCs in terms of cell-based therapies but also for their role as key regulators of the immune response. Video Highlight: https://youtu.be/ceWOIIZd7Jo Abstract : Obesity and T2D disturbs the immune properties of ASCs . It is known that obesity increases proliferation of ASCs but reduces their adipogenic differentiation capacity. This study reveals that ASCs from healthy (lean) individuals exhibit typical immunosuppressive activities such as induction of the M2 macrophage phenotype and suppression of T and B cell proliferation. By contrast, ASCs isolated from obese and T2D subjects promote the M1 macrophage phenotype and are less efficient in suppressing lymphocyte proliferation. Thus, obesity and T2D not only disrupt adipose tissue remodeling but also compromise the immunoregulatory properties of ASCs.